Comparison of PET/MRI with multiparametric MRI in diagnosis of primary prostate cancer: A meta-analysis. Issue 113 (April 2019) - Li, Mou; Huang, Zixing; Yu, Haopeng; Wang, Yi; Zhang, Yongchang; Song, Bin
Abstract: Objective: This meta-analysis aimed to compare the diagnostic performance of positron emission tomography (PET)/MRI using various radiotracers with multiparametric (mp) MRI for detection of primary prostate cancer (PCa). Methods: A systematic literature search up to January 2019 was performed to identify studies that evaluated the diagnostic value of PET/MRI and mpMRI for detection of PCa in the same patient cohorts and had sufficient data to construct 2 × 2 contingency tables for true-positive (TP), false-positive (FP), false-negative (FN), and true-negative (TN) results. The quality of each study was assessed using the Quality Assessment of Diagnostic Accuracy Studies-2 tool, and pooled sensitivity (SEN) and specificity (SPE) were calculated. Summary receiver operating characteristic (ROC) curves and area under the curves (AUCs) were used to compare the performances of PET/MRI and mpMRI. Results: We identified 9 eligible studies that included a total of 353 patients. PET/MRI had a SEN of 0.783 (95% CI, 0.758–0.807) and a SPE of 0.899 (95% CI, 0.879–0.917), and mpMRI had a SEN of 0.603 (95% CI, 0.574–0.631) and a SPE of 0.887 (95% CI, 0.866–0.906). PET/MRI had a higher AUC than mpMRI (0.9311, 95% CI, 0.8990–0.9632 vs. 0.8403, 95% CI, 0.7864–0.8942; P = 0.0036). There was no notable publication bias, but there was medium heterogeneity in outcomes. The meta-regression analysis showed the major potential cause of heterogeneity was the use of region-based rather than lesion-based analysis. Conclusion: PET/MRI has very good diagnostic performance and outperforms mpMRI for the diagnosis of primary PCa.